PENGARUH PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUASAN PEMBELIAN PRODUK SIDOMUNCUL PADA PT BINTANG LIMA DI BATAM - Setiawan, Ervin; Purba, Tiurniari (LPPM Universitas Putera Batam, 2021)
Promotion and quality of products that are well known through social media and word of mouth can be a company's marketing strategy for a product and form a relationship between producer and purchase satisfaction. This study aims to examine and analyze the influence of factors that influence the purchase intention of Sidomuncul products in Batam City. By using non probability sampling, it was obtained 163 respondents. Using multiple linear regression for data analysis and testing the validity, reliability and classical assumptions. This research proves that promotion and product quality can influence purchase intention either partially or simultaneously. From this research, it is expected that companies pay attention to promotion and product quality to increase purchase satisfaction. Keywords: Promotion; Product Quality; Purchase Satisfaction.